Linking chemical and biochemical composition of plant materials to their effects on N2O emissions from a vegetable soil. (December 2016) - Rezaei Rashti, M.; Wang, W.J.; Reeves, S.H.; Harper, S.M.; Moody, P.W.; Chen, C.R.
Abstract: The magnitudes of nitrogen (N) mineralisation and nitrous oxide (N2 O) emissions after the application of plant materials strongly depend on their quality. Despite the existence of some studies in this field, little is known about the underlying mechanisms and regulating factors of these processes, particularly for vegetable cropping systems. In this study, ten typical vegetable and/or vegetable farming rotation plant materials were finely ground, incorporated into the soil and incubated at 25 °C under fluctuating moisture conditions of 55–85% water-filled pore space (WFPS) without N (-N) or with N (+N) addition (100 mg N kg −1 soil as urea). The applied plant materials were characterised using solid state 13 C nuclear magnetic resonance (NMR) spectroscopy and wet-chemical analysis. The dynamics of soil mineral N accumulation and N2 O emissions were monitored over 169 days. Under the -N treatment, plant materials with total N (TN) contents ≥ 27 mg g −1 dry matter produced significantly higher cumulative N2 O emissions than those with TN contents < 27 mg g −1 in the first 105 days of incubation. However, there was no significant difference in cumulative N2 O emissions between these two groups at the end of the experiment due to higher N2 O emissions for plant materials with TN contents <27 mg g −1 during the later stage of the incubation. Under the +N treatment, application of plant materials consistently increased the cumulative N2 O emissions by the end of the incubation compared with the urea only treatment; although a few plant materials resulted in lower or similar N2 O emissions in the initial 2–4 weeks. During the entire incubation, plant materials with high TN contents generally produced higher cumulative N2 O emissions than others in the +N treatment. Stepwise regression analysis indicated a significant correlation between cumulative N2 O emissions and TN, cellulose, lignin, O-aryl C and carbonyl C contents of the plant materials; TN content was the main regulating factor among all chemical and biochemical indices. Highlights: This study related 13 C NMR functional groups of plant materials to N2 O flux. Applied plant materials showed higher cumulative N2 O fluxes than unamended soil. In -N, similar cumulative N2 O emitted from crop residues with different N contents. In +N, all plant materials increased cumulative N2 O fluxes compared with urea only. Cumulative N2 O flux was correlated with plant materials TN and C functional groups.